Occupational safety management system theory and practice - Atabaev M.M; Atabaev K.A; Petrosova L.I (European Journal of Life Safety and Stability (2660-9630), 2021)
The article reveals the essence of the labor protection management system, its structural component, the complex of tasks solved by it, as well as the relationship between its theoretical aspects and practical application. The most important point in the article is determined not by the automatic adherence to labor safety standards and the implementation on their basis of the labor management system, but a more thorough study of these very standards about the price of their transformation and co-progeny based on the own criteria of various enterprises.